2022
DOI: 10.1200/jco.2022.40.16_suppl.1557
|View full text |Cite
|
Sign up to set email alerts
|

Natural language processing of Veterans’ electronic health records to confirm diagnoses of monoclonal gammopathy of undetermined significance.

Abstract: 1557 Background: The Veterans Health Administration (VHA) provides extensive electronic health records (EHRs) on Veterans nationwide. Our prior studies utilized VHA data to study the risk of progression from monoclonal gammopathy of undetermined significance (MGUS) to multiple myeloma. These studies relied on International Classification of Disease (ICD) codes and manual abstraction on clinical notes to both identify and verify MGUS patients. Diagnosis confirmation is necessary because many providers place a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Third, we utilized a highly accurate NLP algorithm to con rm that clinical notes and diagnostic data support the MM diagnoses. [19][20][21][22] We adjusted for known risk factors for MGUS progression including M-protein level, MGUS subtype, and obesity and for the competing risk of death in the analyses. At present, MGUS is managed by annual every 2-3 year follow up with SPEP and/or serum free light chains.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Third, we utilized a highly accurate NLP algorithm to con rm that clinical notes and diagnostic data support the MM diagnoses. [19][20][21][22] We adjusted for known risk factors for MGUS progression including M-protein level, MGUS subtype, and obesity and for the competing risk of death in the analyses. At present, MGUS is managed by annual every 2-3 year follow up with SPEP and/or serum free light chains.…”
Section: Discussionmentioning
confidence: 99%
“…This step is crucial as our prior studies utilizing data abstraction demonstrated that, at best, only 80–84% of patients with ICD codes for MGUS were confirmed to have MGUS on manual chart review. 20 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations